2018
DOI: 10.1017/jfm.2018.491
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion inside a surfactant-laden drop at low surface Péclet numbers

Abstract: We investigate the dynamics of a swimming microorganism inside a surfactant-laden drop for axisymmetric configurations under the assumptions of small Reynolds number and small surface Péclet number $(Pe_{s})$. Expanding the variables in $Pe_{s}$, we solve the Stokes equations for the concentric configuration using Lamb’s general solution, while the dynamic equation for the stream function is solved in the bipolar coordinates for the eccentric configurations. For a two-mode squirmer inside a drop, the surfactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 52 publications
0
26
1
Order By: Relevance
“…Also as (h 2 cosh (2h) − 2h sinh (2h) + h 2 + cosh (2h) − 1) > 0 and (h sinh (2h) − cosh (2h) + 1) > 0, we see that the surfactant redistribution always increases the swimming velocity at small P e s . This is in contrast with the observation that the surfactant redistribution can increase or even decrease the velocity of a swimming microorganism inside a surfactant laden drop at small P e s [20]. These different influences of the surfactant on the swimming velocity, reported in Ref.…”
Section: Limiting Casescontrasting
confidence: 78%
See 2 more Smart Citations
“…Also as (h 2 cosh (2h) − 2h sinh (2h) + h 2 + cosh (2h) − 1) > 0 and (h sinh (2h) − cosh (2h) + 1) > 0, we see that the surfactant redistribution always increases the swimming velocity at small P e s . This is in contrast with the observation that the surfactant redistribution can increase or even decrease the velocity of a swimming microorganism inside a surfactant laden drop at small P e s [20]. These different influences of the surfactant on the swimming velocity, reported in Ref.…”
Section: Limiting Casescontrasting
confidence: 78%
“…These different influences of the surfactant on the swimming velocity, reported in Ref. [20] and this work, might be due to different shapes of the swimmer and the interface used in these two works.…”
Section: Limiting Casesmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, a combination of multipole expansion and Faxén's theorem has been used by Zia and collaborators [41,42], providing the elements of the grand mobility tensor of finitesized particles moving inside a rigid spherical cavity. Additional works addressed the low-Reynolds-number locomotion inside a viscous drop [43][44][45], or the dynamics of a particleencapsulating droplet in flow [46,47]. arXiv:1802.00353v2 [physics.flu-dyn] 14 Aug 2018 Despite enormous studies on particle motion inside a rigid cavity or a viscous drop, to the best of our knowledge, no works have been yet conducted to investigate particle motion inside a deformable elastic cavity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a swimming organism reorients itself and gets scattered from the obstacle or gets trapped or captured by it if the size of the obstacle is large enough and the settling/rising speed of the microorganism is small enough. Near a viscous drop, the surfactant increases the trapping capability [120] and can even break the kinematic reversibility associated with the inertialess realm of swimming microorganisms [123]. In contrast to that, the presence of a surfactant near a planar interface was found not to change the reorientation dynamics [74] but to change the swimming speed [124] in addition to the circling direction [74].…”
Section: Introductionmentioning
confidence: 82%